Qiradh dalam Perspektif Kitab Kifayah Al-Akhyar (Imam Taqiy Ad-Din Al-Hishni Asy-Fi’i) - Luqmanul Hakim; Jamaludin Achmad Kholik (Program Studi Ekonomi Syariah dengan Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2022)
Book of Kifayah al-Akhyar by Imam Taqiy al-Din al-Hishni or his full name with Imam Taqiy al-Din Abu Bakr bin Muhammad al-Husaini ad-Dimasyi is a scholar of fiqh and Sufi scholars who were born in the Shafi'i school of thought who was born in 752 H. and died in the year 829 AH which descended to the Prophet Muhammad. He studied a lot of various scientific disciplines of religion to the great scholars, Some of the works of Imam Taqiy al-Din al-Hishni; Systematic Discussion of the Book of Kifayah al-Akhyar is divided into two chapters; Syarah Method: Halli (elaborating), Providing arguments (istidlal from the Qur'an, as-Sunnah, Ijma 'and Qiyas and explaining a number of hadith lafadz, takhrij hadith, sanad, matan and quality of the hadith), Ta'lil (reasoning) /Critical study in presenting a law, Providing corrections (ta'qib), completing, detailing the law and also criticizing, quoting ikhtilaf and its raw qiq, and explaining common ground. Qiradh: Imam Taqiy ad-Din al-Hishni gives the same understanding between qiradh and mudharabah; Mudharabah in terms is a cooperation agreement between two parties where the first party acts as a provider of capital or shohibul maal, while the second party acts as a manager or mudharib. The profits obtained are divided based on the agreed ratio between shohibul maal and mudharib, while if there is a loss it is borne by shohibul maal except for the negligence of the manager. Mudharabah contracts can be divided into three; 1). Mudharabah Muqayyadah (bound); 2).Mudharabah Mutlaqah (not bound); 3). Mudharabah Musytarakah. Investment products by contract using the mudharabah principle instrument: 1). Mudharabah Bonds; 2). Mudharabah Sukuk; 3). Sharia Mutual Funds; And some Micro Investment products (Tamwil Products).